Comparison of Josamycin and Erythromycin in the Therapy of Mycoplasma pneumoniae Pneumonia - Wenzel, Richard P. (1976)
A controlled, double-blind study was performed to compare the efficacy of two macrolide antibiotics, erythromycin and josamycin, in the therapy of Mycoplasma pneumoniae pneumonia. Marine Corps recruit volunteers received one of the two antibiotics in a dosage of 2 g daily for 7 days. Twelve of 21 men treated with josamycin and 9 of 25 men treated with erythromycin had confirmed M. pneumoniae pneumonia. The josamycin-treated group remained hospitalized for 5.4 ± 1.2 days compared to 5.1 ± 2.0 days for the erythromycin-treated group (0.60 > P > 0.50). Fever days were similar for the josamycin-treated (1.4 ± 0.4) and erythromycin-treated (1.2 ± 0.3) groups (P = 0.95). There was no difference in resolution of signs and symptoms of illness in the two study populations. Thus, josamycin is as efficacious as erythromycin in the therapy of M. pneumoniae pneumonia.